1992
DOI: 10.1146/annurev.mi.46.100192.000433
|View full text |Cite
|
Sign up to set email alerts
|

THE LIPOPHOSPHOGLYCAN OF LEISHMANIA PARASITES

Abstract: Protozoan parasites of the genus Leishmania have the remarkable ability to avoid destruction in the hostile environments they encounter throughout their life cycle. The molecular details of how these pathogens persevere with impunity under harsh conditions are beginning to be understood. The fact that Leishmania parasites have adapted to not only survive, but to proliferate probably is due to the protection conferred by specialized molecules on the parasite's cell surface. One such macromolecule is a novel gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
245
1
6

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 452 publications
(254 citation statements)
references
References 0 publications
2
245
1
6
Order By: Relevance
“…Furthermore, the repetitive structure and glycan modifications associated with many Leishmania spp. cell-surface molecules suggest that these parasites also interact with MR and SR (Turco and Descoteaux, 1992), which have been shown to send a negative signal in other systems.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the repetitive structure and glycan modifications associated with many Leishmania spp. cell-surface molecules suggest that these parasites also interact with MR and SR (Turco and Descoteaux, 1992), which have been shown to send a negative signal in other systems.…”
Section: Discussionmentioning
confidence: 99%
“…Como promastigotes metacíclicos, están listos para ser inoculados en el hospedero mamífero ante una nueva ingestión de sangre por el vector (7,19). estudiadas, caracterizadas y asociadas con la metaciclogénesis son el LPG (22,23) y la glicoproteína gp63 (24,25), expresadas abundantemente en la superficie de los promastigotes, principalmente en cepas del subgénero Leishmania, pero que sufren una considerable disminución o están ausentes, según la especie, en el estadio de amastigote (23). En el subgénero Leishmania, el LPG se expresa sobre toda la superficie del promastigote, incluido el flagelo, y está organizado como un filamento densamente empaquetado que forma un glicocálix.…”
Section: Cambios Morfológicos Genéticos Y Bioquímicos Asociados Con unclassified
“…Por su parte, el LPG, un factor de virulencia multifuncional al menos en L. major, se ha implicado en varios procesos que conllevan a la desactivación del macrófago, como es la inhibición de la proteína cinasa C (63,64), la cual está relacionada con la respuesta oxidativa del macrófago. Además, se ha visto que el LPG inhibe la fusión fagosoma-endosoma (65) y elimina eficientemente metabolitos tóxicos del oxígeno como el anión superóxido y radicales hidroxilos (23). La inhibición transitoria de la fusión fagosoma-endosoma puede entenderse como una estrategia del parásito para ganar tiempo hasta transformarse en amastigote, el cual es más resistente a enzimas hidrolíticas y al pH ácido encontrado en el fagolisosoma una vez ocurre la fusión fagosoma-endosoma.…”
Section: Implicaciones De La Metaciclogénesis En El Ciclo De Vida De unclassified
“…More recently the glycoinositolphospholipids (GIPLs) received great attention since it was demonstrated that they act as anchors of proteins on the eukaryotic cell membrane and, for instance, of a phosphosaccharide in Leishmania (Turco & Descoteaux 1992).…”
Section: Lppg and Galactofuranosementioning
confidence: 99%
“…It is interesting to note that in all GIPLs, furanoic galactose, when present, is bound to an α-D-mannose by a β1→3 bond, as a non reducing terminal sugar -as in LPPG (Lederkremer et al 1985b, Previato et al 1990, Carreira et al 1996) -or as an internal unit inside an oligosaccharide chain -as in Leishmania LPG (Turco & Descoteaux 1992). That specificity suggests the existence of a β(1-3) galactofuranosyltransferase for biosynthesis and a β(1-3) galactofuranosyl hydrolase for degradation.…”
Section: Lppg and Galactofuranosementioning
confidence: 99%